INSTILLING CHARACTER EDUCATION FROM AN EARLY AGE BY MAKING A HABIT OF SAYING POSITIVE WORDS BEFORE ENTERING CLASS - Subaita; Iswatiningsih , Daroe (Al-Mubin, 2025)
Early Childhood Education (PAUD) has a crucial role in instilling character from an early age. This article reviews the application of the habit of saying positive words as a form of affirmative strategy to build confidence, optimism, and positive mindset in children at ABA 01 Batu Kindergarten. Through daily activities such as morning welcomes, a fun approach and parental participation, these habits are able to create a learning environment that supports and strengthens children's social and emotional development. The results of the evaluation showed an increase in confidence, enthusiasm for learning, and children's ability to establish healthy social relationships. Obstacles that arise, such as children's limited understanding of the meaning of affirmation and challenges in maintaining consistency of practice, are overcome through easy-to-understand explanations and active involvement of parents. This article concludes that getting children used to saying positive words is a simple method but has a great effect on shaping children's character as a whole and continuously